The Optimum Life of a Patent When the Timing of Innovations is Stochastic - Vincenzo Denicolò (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
This paper studies the optimal lifetime of a patent in a model where the timing of innovatons: is uncertain. We assume a Poisson discovery process with a linear hazard function and contractural R&D costs. The invention industry is modelled in three alternative ways: i) monopoly; ii) oligopoly with free entry; iii) perfect competition. Several comparative staties results are derived.
Keywords: 330